A STUDY OF MICRO COFFEE SHOPS: UNPACKING THE DIMENSION OF PERCEIVED VALUE IN BUILDING BRAND LOYALTY WITH CUSTOMER SATISFACTION AS MEDIATOR - Sastrawan, Ni made devi angelina; Prasiwi Bestari, Ni Made (International Journal of Global Accounting, Management, Education, and Entrepreneurship, 2025)
This study aims to examine the dimensions of perceived value; emotional value, social value, functional value (value for money), and functional value (quality) in influencing brand loyalty with customer satisfaction as a mediating variable among micro coffee shop customers in Bali. The research focuses on three micro coffee shops in three cities with most coffee shop population in Bali; Courtside Bre (Denpasar), Pesona by The Bay (Badung), and Selesai Coffee & Memory (Gianyar). The sample consists of 108 respondent’s selected using purposive sampling, targeting individuals who have visited these coffee shops at least twice. The data were analyzed using the Partial Least Squares-Structural Equation Modelling (PLS-SEM) method with SmartPLSsoftware.The results reveal that emotional value and social value have a significant and positive impact on customer satisfaction, which in turn strongly influences brand loyalty. Moreover, customer satisfaction effectively mediates the relationship between emotional and social values and brand loyalty. Conversely, functional value both value for money and quality does not have a significant effect on customer satisfaction or brand loyalty, either directly or through mediation. These findings suggest that micro coffee shop customers in Bali are primarily driven by emotional and social experiences rather than rational or price-based considerations. Therefore, enhancing emotional engagement, creating a comfortable atmosphere, and fostering social interaction are key strategies for building customer satisfaction and brand loyalty in the micro coffee shop industry.